The Utilization of Crushed Corn Cob as a Sand Substitute in Portland Cement Mortars for Sustainable Construction - Ana Torre; Sorin Ramirez; Isabel Moromi; Ladislao Basurto; Carmen Reyes (Buildings, 2024)
The utilization of mineralized sandy shredded corn cob (SCC) as a partial replacement for fine aggregate in Portland cement mortars (PM) presents an innovative opportunity for sustainable construction and organic waste reutilization. This study aims to assess the impact of SCC, with granulometric variations G1 and G2, on eight mortar formulations (PM, SCC-G1-5%, SCC-G1-10%; SCC-G2-5%, SCC-G2-10%, SCC-G2-15%, SCC-G2-20%, and SCC-G2-30%) with a consistent water-to-cement ratio of 0.55. Fresh-state properties (flowability, temperature, pH, unit weight, and setting time) and hardened-state characteristics (compressive strength at 4, 7, 14, and 28 days) were evaluated. Notably, flowability decreased by 90% for G2 designs with up to 15% SCC, unit weight decreased by up to 12% with SCC-G2-30%, setting time was delayed, and compressive strength for all SCC mortars up to 20% exceeded 21.9 MPa. In conclusion, the partial replacement of sand with a G2 particle-size distribution of SCC is feasible, with an optimal performance observed in SCC-G2-5%.